Relationship Between Pain Severity and Magnetic Resonance Imaging Features in Patients with Osteoarthritis of The Knee - Ayhan Bilgici; Cengizhan Doğan; Erhan Çil; Şükran Sakarya; Ömer Kuru; Mustafa Bekir Selçuk (Archives of Rheumatology, 2010)
Objective: To evaluate the association between clinical symptoms and magnetic resonance imaging (MRI) findings in patients with osteoarthritis (OA) of the knee. Materials and Methods: Ten men and 24 women between 30 and 60 years of age, who fulfilled the American College of Rheumatology (ACR) criteria for knee OA, were included in the study. All patients underwent MRI of the more symptomatic knee and the MRI findings were evaluated by the same radiologist blinded to clinical findings, using a semi-quantitative whole-organ MRI scoring method (WORMS). The Western Ontario and Mc-Master University (WOMAC) osteoarthritis index was used to assess physical function, morning stiffness, and joint pain. Results: Linear regression analysis revealed that the total WORMS score and effusion severity were the most important predictors of the WOMAC pain score. The volume of the effusion was significantly correlated with the WOMAC pain and disability scores (r=0.601, p<0.001; and r=0.626 p<0.001, respectively). There was also a positive correlation between the WOMAC pain score and the WORMS bone marrow edema (BME) score (r=0.508, p<0.01). Patients with synovial effusions had significantly higher WOMAC pain and disability scores compared to patients without synovial effusions (p<0.01 and p<0.001, respectively). Similar results were also observed in patients with BME compared to those without edema. Conclusion: Our results demonstrated that the severity of synovial effusion on MRI was associated with increased pain and disability in knee OA. MRI allows the precise visualization of joint structures, such as cartilage, bone, synovium, ligaments, and menisci, so that the joint can be examined as a whole organ. (Turk J Rheumatol 2010; 25: 184-90)